Assessing trace-elements as indicators of marine finfish aquaculture across three distinct Canadian coastal regions. (August 2021) - Hamoutene, D.; Hua, K.; Lacoursière-Roussel, A.; Page, F.; Baillie, S.M.; Brager, L.; Salvo, F.; Coyle, T.; Chernoff, K.; Black, M.; Wong, D.; Nelson, E.; et al.
Abstract: Several trace-elements have been identified as indicators of finfish aquaculture organic enrichment. In this study, sediment sampling at finfish farms was completed as part of an Aquaculture Monitoring Program in three distinct Canadian regions. Despite diverse datasets, multivariate analyses show a consistent clustering of known direct (Cu and Zn) and indirect (Cd, Mo and U) tracers of aquaculture activities with sediment organic matter (OM) and/or total dissolved sulfides concentrations. OM content was also a predictor of Cu, Zn, Mo and U concentrations according to decision tree analyses. Distance from cages did not emerge as a strong driver of differences among sampling points; however, a tendency towards negative associations is clear especially for Zn. Enriched stations as determined after geochemical normalization were mostly localized within 150 m of net-pens. Selected trace-elements (in particular Zn) can be useful indicators of aquaculture organic enrichment in different ecosystems and valuable tools for monitoring programs. Highlights: Sediment sampling at finfish farms was completed in three distinct Canadian regions. Multivariate analyses show a clustering of Cu, Zn, Cd, Mo and U with sediment organic matter and/or total dissolved sulfides. Organic matter content is a predictor of Cu, Zn, Mo and U concentrations as per decision tree analyses. Enriched stations in selected trace-metals were localized within 150 m of net-pens. Selected trace-elements (in particular Zn) are useful indicators of aquaculture organic enrichment.